Estudo da oscilação de neutrinos muônicos usando dados atmosféricos e de acelerador nos experimentos MINOS e MINOS+ - Medeiros, Michelle Mesquita de (2015)
The MINOS (Main Injector Neutrino Oscillation Search) and MINOS+ experiments were designed to study neutrino oscillations using a muon neutrino beam which is detected in two different locations, in the Near Detector and in the Far Detector. The distance between the detectors allows the beam neutrinos to oscillate to a different flavor. Therefore, a disappearance of the muon neutrinos from the beam is observed in the Far Detector. The Far Detector has a special apparatus which makes possible the selection of atmospheric neutrinos and antineutrinos. These come from interactions of cosmic rays with the Earth’s atmosphere. Both detectors have a magnetic field, allowing the distiction between neutrinos and antineutrinos interactions. This thesis presents the first combined analysis of data from the MINOS and MINOS+ experiments. We have analyzed the combined neutrino energy spectrum from the complete MINOS beam data and the first, more energetic, MINOS+ beam data. The disappearance of the muon neutrinos was observed and the data has shown to be congruent with the oscillation model. Beyond that, we have measured the atmospheric oscillation parameters of the beam and atmospheric neutrinos and antineutrinos from MINOS combined with the atmospheric neutrinos and antineutrinos from MINOS+. Assuming the same oscillation parameters for both neutrinos and antineutrinos, the best fit is obtained for inverted hierarchy and lower octant with m2 32 = 2:37 103 eV2 and sin2 23 = 0:43, and the limits m2 32 = [2,29 - 2,49] 103 eV2 (68%) and sin2 23 = 0.36 - 0.66 (90%). These results are the most precise measurement of the neutrinos mass splitting using muon neutrino disappearance data only.